Retrospective estimation of values for total lung capacity by plethysmography, helium gas dilution, and chest radiography in patients with cystic fibrosis. - Cutrera, R (1988)
In children with cystic fibrosis, total lung capacity was estimated by helium dilution, plethysmography, and radiography. None of these methods should be used interchangeably as the 95% confidence intervals for estimating were large at 58-144% for radiography and 45.3-100.4% for helium dilution.